An ultrasensitive colorimetric sensor for efficient detection of Hg2+ at physiological pH. Issue 6 (20th February 2015) - Nanda Kumar, D.; Rajeshwari, A.; Alex, Sruthi Ann; Chandrasekaran, N.; Mukherjee, Amitava
Abstract : The estimation of Hg 2+ in a buffer system (Tris buffer; pH 7.4) has been performed using a novel, enzyme-based, indirect detection method with the aid of non-functionalized AgNPs. Abstract : The estimation of Hg 2+ in a buffer system (Tris buffer; pH 7.4) has been performed using a novel, enzyme-based, indirect detection method with the aid of non-functionalized AgNPs. The designed system has a good linear correlation ( R 2 = 0.9759) in the range of 1 to 10 × 10 −12 M. The probe was shown to possess an extremely low limit of detection of 1.304 × 10 −12 M, which is the lowest reported for the detection of Hg 2+ at physiological pH (7.4). The probe was found to have good recovery rates when tested with Simulated Body Fluids (SBFs).